ECONOMIC VALUE AND RICE-FISH PACET RAP BANDUNG - Nindya dendrania fitra; kastana sapanli (Universitas Djuanda, 2019)
Pacet Subdistrict is one of the areas in Bandung Regency that applies the concept of Rice-fish farming. Rice-fish farming uses some different inputs with monoculture farming because this farming requires more production factor costs. Various aspects can be reviewed in research on rice-fish farming, especially economic aspects because it is very closely related to community welfare and ecological benefits. The potential of rice-fish farming has been widely studied, but the analysis of income and sustainability status of the farm is not known more detailed yet. Therefore, this study aims: (1) Analyzing the patterns of rice-fish farming, (2) Analyzing the income of rice-fish farming in Pacet Subdistrict, Bandung Regency, and (3) Knowing the value of the sustainability index of rice-fish farming in Pacet Subdistrict, Bandung Regency. The methods that used in this study are descriptive analysis, income analysis, and Multi-Dimensional Scaling (MDS). The results showed that the rice-fish farming pattern basically had similarities with monoculture farming, but one of the different is in the land processing process which consists of making caren activities for living fish. The receipts earned on rice-fish farming are Rp 21.716.560,0 per hectare per planting season. Rice-fish farmers earn income from cash costs with a value of Rp 9.180.524,1 and income from total costs Rp 7.888.605,6. The value of the R/C ratio for cash costs is 1,73 and R/C for total costs is 1,57. The sustainability index of rice-fish farming is 54,88 which indicates a fairly sustainable status.Keywords: MDS, income, farming pattern, rap rice-fish, rice-fish farming